DRP5 is involved in cancer cell growth and predicts poor prognosis in human osteosarcoma. (4th April 2017) - Wang, Lin; Liu, Weihai; Tang, Hengtao; Xie, Xianbiao; Zou, Changye; Wang, Yongqian; Gao, Zhenhua; Yin, Junqiang
Abstract: Osteosarcoma is an extremely aggressive primary malignant bone tumor of childhood. Collapsin response mediator proteins (CRMPs), which are highly expressed in the developing nervous system, were recently shown to be associated with cancer development. However, the relationship between DRP5 (CRMP5) and osteosarcoma has not been evaluated. In this study, we investigated the role of DRP5 in the regulation of osteosarcoma growth. DRP5 mRNA and protein levels were significantly upregulated in human osteosarcoma cell lines and associated with increased migration and invasion. Genetic knockdown of DRP5 markedly suppressed the expression of matrix metalloproteinase (MMP)‐2 and MMP‐9. DRP5 silencing significantly inhibited osteosarcoma cell growth in vitro and in a xenograft mouse model in vivo. Microarray immunohistochemical analysis of osteosarcoma specimens and Kaplan–Meier analysis showed that patients with high DRP5 protein expression had shorter overall survival than those with low DRP5 levels. Taken together, these results suggest that DRP5 plays a critical role in the regulation of osteosarcoma and could be a potential therapeutic target and prognostic factor in osteosarcoma. Abstract : DRP5 plays a critical role in the regulation of osteosarcoma and may be a potential therapeutic target and a new prognosis factor for the treatment of osteosarcoma.